The Role of Tafsir Tarbawi Values in the Character Development of Students - Budi Sihabudin; Iskandar Mirza (Kasyafa: Jurnal Pendidikan Agama Islam, 2025)
Character education is a crucial element in forming a generation that is moral, has integrity and excels. The values of tarbawi interpretation, namely the interpretation of verses from the Koran using an educational approach, have a significant contribution in developing students' character. This research aims to explore the role of tarbawi tafsir values in character formation and their impact on developing the personality of students with noble character. The research method used is a qualitative approach through literature analysis and case studies in educational institutions that integrate Islamic values in the learning process. Research findings reveal that values such as honesty, responsibility, tolerance and hard work, which are implemented through tarbawi interpretation, are able to instill positive character in students. These values are applied through Qur'an-based learning, good behavior habits, and strengthening the role of teachers as role models. The research results recommend that the values of tarbawi interpretation need to be used as a basis for developing character education curricula in order to produce a superior generation, both intellectually, spiritually and morally.